Dark Chocolate: A Review on the Effect of Functional Ingredient Substitution on Physicochemical Properties, Sensorial Acceptance and Potential Health Benefits - Mohd Saupi, Intan Anis; Mhd Jalil, Abbe Maleyki; Hussin, Napisah (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2025)
This scoping review aimed to evaluate evidence from 2013 to 2024 on the impact of substituting functional ingredients in dark chocolates in terms of their physicochemical properties, sensory acceptance, and potential health benefits. A literature search was performed using electronic databases including PubMed (National Library of Medicine), Science Direct (Elsevier), and Scopus (Elsevier), using data from 2013 to 2024. All types of studies published in English, excluding systematic reviews or review papers, were eligible for inclusion. A total of 1,067 eligible studies were identified, 24 of which met the inclusion criteria. This review highlights trends and existing gaps, and provides valuable insights for researchers, industry professionals, and consumers interested in chocolate formulation and consumption. The findings indicate that incorporating functional ingredients, such as fibres, polyphenols, and probiotics, can enhance the nutritional profile of dietary fibre, antioxidant activity, and gut health effect from dark chocolate. However, these substitutions are negatively affected by decreasing physical properties (e.g., hardness, viscosity, and melting temperature) and sensory attributes such as flavour and texture. This review shows that, although substituting functional ingredients improves nutritional quality, it negatively affects sensory characteristics and poses a significant challenge to consumers. Further research should explore novel ingredients to optimise nutritional profiles, increase health benefits, and improve sensory attributes of chocolate products.